Effectiveness Project Based Learning (PJBL) Model on Social Sciences Learning Outcomes in class IV of Gugus Ki Hajar Dewantara Bumi Raya District, Morowali Regency - Suriastini, Ni Kadek; Hasan, Hasan; Idrus, Idrus (Journal of Education Method and Learning Strategy, 2024)
As it goes time, the curriculum in Indonesia has experience Lots development. The 2013 curriculum is curriculum newly designed based on paradigm education 21st century. Development curriculum the join in change load as well as the learning model used. A creative and prioritizing learning process experience personal (observing, asking, reasoning, and trying) is needed for support activity learning based 2013 curriculum. As for the formulation problems in research This Is the Project Based Learning (PJBL) learning model effective to results students studying social studies in class IV of the Ki Hajar Dewantara cluster Bumi Raya District, Regency Morowali, As for the objectives of the research .This for now effectiveness of the Project Based Learning (PJBL) model on results Study students in social studies learning in class IV of the Ki Hajar Dewantara cluster Bumi Raya District, Regency Morowali. The method used​ is Study quantitative can interpreted as method research based on philosophy​ positivism, used For research on populations or sample specific, data collection. Results Then you can concluded that effective use of the Project based learning model For increase results learn by eye social studies lessons in class 4 of the Ki Hajar Dewantara group Bumi Raya District, Morowali Regency. Temporary use method conventional No effective For increase results studying social studies in class IV of the Ki Hajar Dewantara cluster Bumi Raya District, Morowali Regency.